Development of Diabetes Mellitus Medication Compliance Instrument - Faza Khilwan Amna; Irwan Budiono; Eko Farida (Indonesian Journal of Global Health Research, 2025)
Medication adherence is an important factor in the management of type 2 DM. Non-adherence in taking medication can worsen the patient's health condition, increase glycated hemoglobin (HbA1c) levels , and increase the risk of complications such as neuropathy, nephropathy, and cardiovascular disease. Research shows that only about 50-60% of patients comply with prescribed medication.The aim of this research is to develop a research instrument on medication adherence in Diabetes Mellitus patients. The type of research used is Research and Development . To produce a research instrument product on compliance with taking diabetes mellitus medication and to test its effectiveness, the research process is carried out through two main stages, namely the content validity stage and the validity and reliability test stage. Content validity is evaluated by 10 expect panels. While the validity and reliability tests were carried out on 30 respondents, namely Type 2 Diabetes Mellitus patients aged 19-40 years who are outpatients in Mardhatillah Hospital Pemalang, Central Java. Validity test analysis using Pearson Product Moment correlation (r) by looking at the output results of Corrected Item Total Correlation , while the Reliability Test is measured by the Cronbach Alpha statistical test. The results of this study indicate that all items in the diabetes mellitus medication adherence instrument meet the content validity criteria based on the assessment. for expert (I-CVI ≥ 0.75). Furthermore, based on the validity test of 15 question items, it is known that for statements 1 to 15, the lowest calculated r is 0.436 and the highest calculated r is 0.779, so that the 15 statements of the DM medication adherence questionnaire are valid. Meanwhile, the results of the reliability test on the 15 items of this research questionnaire have a total Cronbach's Alpha value per variable > 0.60, so that the research questionnaire is reliable (consistent). The research instrument in the form of a questionnaire on adherence to taking DM medication consisting of 15 questions was declared to meet the criteria of content validity , validity and reliability , so it can be used as a research instrument. With valid and reliable instruments, health workers can monitor patient compliance more effectively, support the success of therapy and improve the quality of life of patients with diabetes mellitus.